Bridging the gap between education and appropriate use of benzodiazepines in psychiatric clinical practice - Dell’Osso B (Dove Medical Press, 2015)
Bernardo Dell’Osso,1,2,* Umberto Albert,3,* Anna Rita Atti,4 Claudia Carmassi,5 Giuseppe Carrà,6 Fiammetta Cosci,7 Valeria Del Vecchio,8 Marco Di Nicola,9 Silvia Ferrari,10 Arianna Goracci,11 Felice Iasevoli,12 Mario Luciano,8 Giovanni Martinotti,13 Maria Giulia Nanni,14 Alessandra Nivoli,15,16 Federica Pinna,17 Nicola Poloni,18 Maurizio Pompili,19 Gaia Sampogna,8 Ilaria Tarricone,20 Sarah Tosato,21 Umberto Volpe,8 Andrea Fiorillo8 1Department of Psychiatry, University of Milan, Fondazione IRCCS Ca’ Granda, Ospedale Maggiore Policlinico, Milan, Italy; 2Bipolar Disorders Clinic, Stanford Medical School, Stanford University, CA, USA; 3Rita Levi Montalcini Department of Neuroscience, University of Turin, Torino, 4Department of Biomedical and NeuroMotor Sciences, University of Bologna, Bologna, 5Department of Clinical and Experimental Medicine, University of Pisa, Pisa, Italy; 6Division of Psychiatry, Faculty of Brain Sciences, University College London, London, UK; 7Department of Health Sciences, University of Florence, Florence, 8Department of Psychiatry, University of Naples SUN, Naples, 9Institute of Psychiatry and Psychology, Catholic University of Sacred Heart, Rome, 10Department of Diagnostic-Clinical Medicine and Public Health, University of Modena and Reggio Emilia, Modena, 11Department of Molecular Medicine and Clinical Department of Mental Health, University of Siena, Siena, 12Department of Neuroscience, Reproductive Sciences and Odontostomatology, University Federico II of Naples, Naples, 13Department of Neuroscience, Imaging, and Clinical Science, University G.d Annunzio, Chieti-Pescara, 14Section of Psychiatry, Department of Biomedical and Specialty Surgical Sciences, University of Ferrara, Ferrara, 15Psychiatric Institute, Department of Clinical and Experimental Medicine, University of Sassari, Sassari, Italy; 16Bipolar Disorder Unit, CIBERSAM, IDIBAPS, Hospital Clinic, University of Barcelona, Barcelona, Spain; 17Department of Public Health, Clinical and Molecular Medicine, Unit of Psychiatry, University of Cagliari, Cagliari, 18Department of Clinical and Experimental Medicine, Psychiatric Division, University of Insubria, Varese, 19Department of Neurosciences, Mental Health and Sensory Organs, Suicide Prevention Center, Sant’ Andrea Hospital, Sapienza University of Rome, Rome, 20Department of Medical and Surgical Sciences, Bologna University, Bologna, 21Section of Psychiatry, Department of Public Health and Community Medicine, University of Verona, Verona, Italy *These authors contributed equally as first authors Abstract: More than half a century after their discovery, benzodiazepines (BDZs) still represent one of the largest and most widely prescribed groups of psychotropic compounds, not only in clinical psychiatry but also in the entire medical field. Over the last two decades, however, there has been an increased focus on the development of antidepressants and antipsychotics on the part of the pharmaceutical industry, clinicians, and researchers, with a reduced interest in BDZs, in spite of their widespread clinical use. As a consequence, many psychiatric residents, medical students, nurses, and other mental health professionals might receive poor academic teaching and training regarding these agents, and have the false impression that BDZs represent an outdated chapter in clinical psychopharmacology. However, recent advances in the field, including findings concerning epidemiology, addiction risk, and drug interactions, as well as the introduction of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition with related diagnostic changes, strongly encourage an updated appraisal of the use of BDZs in clinical practice. During a recent thematic event convened with the aim of approaching this topic in a critical manner, a group of young Italian psychiatrists attempted to highlight possible flaws in current teaching pathways, identify the main clinical pros and cons regarding current use of BDZs in clinical practice, and provide an updated overview of their use across specific clinical areas and patient populations. The main results are presented and discussed in this review. Keywords: benzodiazepines, psychiatric clinical practice, teaching issues, risks and benefits